ImmersiveBuild: The Applications of Virtual Reality and Treadmills for the Renovation of Educational Buildings - Long, Elizabeth; Li, Richard Z.; Nichols, Jack; Hou, Yu; Li, Shuai (2024 IEEE 3rd International Conference on Intelligent Reality (ICIR), 2024)
With school renovations, upgrades to classroom layouts can help students learn more efficiently. However, the traditional requests for information from building occupants, such as students, staff, and faculty members, are based on 2D drawings or 3D models. Occupants may not understand blueprints or express their true feelings. They need to experience the environment and provide feedback about the renovation plans. This research combined Virtual Reality (VR) software and all-directional treadmill hardware to build an ImmersiveBuild platform for participants to sense the environment and evaluate the renovation plans. Our experiments show that the walk-through virtual environment influenced participants' decisions, and participants' physiological data records, such as the heartbeat rate, indicated their involvement and immersion. The ImmersiveBuild has a potential application for future architecture and construction industries in communicating with building occupants to collect feedback on renovation designs.